Zero Waste-Oriented Adiwiyata Program in Developing Environmental Care Character of Madrasah Ibtidaiyah Students - Maulani, Nini; Balqis, Rizqiyah Ratu (Universitas Islam Indonesia, 2026)
Managing plastic waste is still a big environmental problem, especially in schools where students need to learn to care about the environment from a young age. This study investigates the execution of a zero waste-oriented Adiwiyata program at an Islamic elementary school, emphasising the incorporation of zero waste principles, engagement with the school ecosystem, and the cultivation of students' environmental stewardship character. A descriptive qualitative methodology was utilised, involving 28 informants chosen via purposive sampling. We gathered data through interviews, observations, and documents, and we used the Miles and Huberman interactive model with triangulation to analyse it. The results indicate that zero waste practices, including the utilisation of personal eating utensils, daily waste sorting, and environmental activities, were effectively incorporated into the school culture through consistent habituation, promoting the internalisation of 3R principles. The program worked better because the school ecosystem, especially the students, was actively involved. The program helped cut down on plastic waste and make students more aware of the environment and more responsible. Internal commitment was more important than external funding. This research presents an innovative contribution by showcasing an integrated model of zero waste, Adiwiyata, and Islamic value-based character education at the Madrasah Ibtidaiyah level, emphasising its potential as a replicable framework for sustainability-oriented education.